Analisis Pengendalian Piutang Untuk Meminimalisir Resiko Piutang Tak Tertagih Pada Koperasi Serba Usaha Artha Guna Kwaron - Ari Teguh Sabar Arianto (JFAS : Journal of Finance and Accounting Studies, 2021)
Abstract Receivables are the company's assets to clients or customers on credit sales of goods or services which are also used as information to interpret financial statements. If it is due, however, the debtor does not pay it, it is called a bad debt. This study aims to analyze the control of accounts receivable to minimize the risk of bad debts at KSU Artha Guna. The method in writing this essay has used descriptive methods, namely analyzing data by determining, collecting, completing, analyzing and giving opinions so as to produce a clear picture of the control of accounts receivable against the risk of bad debts. The results of this study indicate that at KSU Artha Guna using the semi-joint responsibility method, the group leader is fully responsible for the customer. From the data obtained in 2017-2019, the bad debts are 0% or from the data obtained from 2017-2019 the accounts are fully collectible. So it can be concluded that the method used by KSU Artha Guna has been implemented well.